Clinical-epidemiological characteristics of hypertensive patients at a Family Doctor's Office in Santa Clara - Carlos Enrique Cruz Cararzana; Claudia García Carrazana (Universidad de Ciencias Médicas de Granma, 2020)
High blood pressure is a chronic non-transmittable disease, which is also a risk factor for the development of other clinical conditions. The incidence of arterial hypertension in the Cuban population is high. Aim: to characterize the evolution of arterial hypertension in a Family Doctor's Office. Methods: an observational, descriptive and cross-sectional study was carried out at the Family Doctor's Office 17-19 in the municipality of Santa Clara. The study covered the months of January to March 2020. Of the 256 hypertensive patients, a sample of 52 was selected by a simple random method. Results: Males predominated (53.84 %), together with the age group between 40 and 49 years (28.84 %). A total of 63.46 % of the patients were white-skinned. 51.61% presented risk factors. The risk factors with the highest incidence were smoking, followed by obesity and sedentary lifestyle. Conclusions: the most affected hypertensive patients are male. Most patients have a family history of high blood pressure. Smoking is a high incidence risk factor in the hypertensive population.